C = 1995 x 1995
= (1991+4) x 1995
= 1991 x 1995 + 4 x 1995 (1)
D = 1991 x 1999
= 1991 x (1995+4)
= 1991 x 1995 + 1991 x 4 ( 2)
từ (1) và (2) => C > D
A=1991x1999=(1995-4)1999=1995x1999-4x1999
B=1995x1995=1995x(1999-4)=1995x1999-1995x4>1995x1999-4x1999=A
vậy A<B
C = 1995 x 1995 = (1991+4) x 1995 = 1991 x 1995 + 4 x 1995
D = 1991 x 1999 = 1991 x (1995+4) = 1991 x 1995 + 1991 x 4
Ta có :
C = 1991 x 1995 + 4 x 1995
D= 1991 x 1995 + 1991 x 4
Ta tách :
C = (1991 x 1995) + (4 x 1995 )
D = (1991 x 1995 )+ (1991 x 4 )
C và D có vế (1991 x 1995) giống nhau nên ta loại bỏ
Còn (4 x 1995 ) của C và (1991 x 4 ) của D
Mà (4 x 1995 ) > (1991 x 4 )
Nên C > D ( C lớn hơn D )
Chúc em làm bài tốt